The effect of implantoplasty on dental implant fracture resistance: a systematic review - Goh, Rayner; Tawse-Smith, Andrew; Atieh, Momen; Duncan, Warwick; Ma, Sunyoung; Li, Kai Chun (IIUM Journal of Orofacial and Health Sciences, 2022)
An increase in dental implant placements in recent years has seen a growth in the reported cases of post-operative complications such as peri-implantitis. One of the available treatment modalities to overcome such complications is implantoplasty. Although this procedure is not new, the long-term effect of implantoplasty has not been addressed extensively. The aim of this systematic review was to investigate the change in fracture resistance of dental implants after implantoplasty. Three electronic databases and reference lists of included studies were searched to assess the potential effect of implantoplasty on implant fracture resistance. Titles and abstracts were screened by two reviewers in parallel. The extracted information regarding implant fracture resistance was reported based on the guidelines set by the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) statement. A total of 56 studies were identified, of which, nine studies were included. Narrow platform implants (<3.75 mm) were more susceptible to fracture following implantoplasty compared to wider platforms (?5 mm). Implants with internal hexagon connection may have a higher risk of fracture after implantoplasty compared to other connection designs such as external hexagon and conical connections. Other potential factors which may affect implant fracture resistance after implantoplasty include crown to implant ratio, implant material, and the amount of peri-implant bone loss. Within the limitation of in vitro studies, there is no clear evidence to demonstrate the effect of implantoplasty on implant fracture resistance. Methodological differences between the available studies did not allow for clear comparison between them. Furthermore, the limited amount of clinical reports of this resective procedure, in combination with patient and operator variability, affect the clinical assessment of this treatment modality.